TINJAUAN YURIDIS PERLINDUNGAN HUKUM BAGI NASABAH FINANSIAL ATAS TINDAK PIDANA PENGGELAPAN DANA OLEH DEBT COLLECTOR - Erlina Chusnova Bulan (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTIONEmbezzlement of fund done by some collector debt really make all client and company of their place work to lose because action which they can smear good name institute or the company particularly again client which not know something will meet the competitor.  With existence of protection of law to client hence embezzlement, theft and deception conducted by some potency collector debt oknum will be low because seen performance of debt guarantees and collector and also Legislation going into effect. Key words: protection of law to client of financial, Collector Debt.